Use of Property for Retirement. Supplementary Paper to the Final Report of the Pensions Working Group (Central Bank of Malta, 2005)
This paper aims to answer two questions - (i) is property savings a viable alternative source of retirement income? and (ii) how can property be used to fund retirement income, if at all? A brief analysis of statistics regarding, amongst others, personal savings, household debts and property prices and ownership, seems to indicate that an element of savings have been targeted towards housing. In addition, while no data is available as to what percentage of household assets are in housing assets, it is likely that housing assets may represent a high percentage of household wealth given the trend of rising property prices in Malta over the recent years. (...)
Keywords: 330